The evolution of immigrants' homeownership in Germany - Dorothee Ihley; Andrea Siebert-Meyerhoff (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2016)
Recently, homeownership rates of migrants in Germany increased by more than 10 percentage points. To shed light on this sharp increase, this paper investigates the change in homeownership rates of immigrant households in Germany between 1996 to 2005 and 2000 to 2012 respectively using a probit-based non-linear decomposition method. Empirical findings suggest that 50 percent of the change in immigrant's homeownership rate within the first time period can be explained by characteristics, especially by age and educational attainment. In the second time period, the explanatory power of characteristics is almost zero indicating that it is the favorable economic environment during that time that is responsible for the increase in homeownership of immigrant households in Germany.
Keywords: F22; J15; R21; 330; Homeownership; International Migration; Germany